ANALISIS PENGARUH FRAUD HEXAGON TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Nurjian Anggraini, Dias; Azizah, Widyaningsih; Damayanti, Ameilia (FEB-UP Press, 2025)
This research aims to analyze the factors that drive Financial Statement Fraud using Fraud Hexagon analysis. This study analyzes stimulus proxied by financial stability, opportunity proxied by ineffective monitoring, rationalization proxied by quality change in auditor, capability proxied by change in director, arrogance proxied by frequent number of CEO's picture, and collusion proxied by political connection towards financial statement fraud. Based on the results of the purposive sampling method, 36 banking sector companies were obtained that met the sample criteria. The analysis method used is panel data logistic regression analysis through the Eviews 12 application. The results showed that frequent number of CEO' picture has an effect on financial statement fraud. While financial stability, ineffective monitoring, change in auditor, change in director and political connection do not affect the potential for financial statement fraud.